Bioenergetics and Autophagic Imbalance in Patients-Derived Cell Models of Parkinson Disease Supports Systemic Dysfunction in Neurodegeneration - González-Casacuberta, Ingrid; Juárez-Flores, Diana Luz; Morén, Constanza; Garrabou, Gloria (Frontiers in Neuroscience, 2019)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder worldwide. This prevalence is expected to rise as life expectancy increases and diagnostic and therapeutic protocols improve. PD encompasses a multitude of clinical, genetic and molecular forms of disease. Even though the mechanistic events leading to neurodegeneration remain unknown, some molecular hallmarks have been reported in most patients and models of the disease. Neuroinflammation, protein misfolding, disrupted endoplasmic reticulum-mitochondria crosstalk, mitochondrial dysfunction and consequent bioenergetic failure, oxidative stress and autophagy deregulation, are amongst the most commonly described. Supporting these findings, numerous familial forms of PD are caused by mutations in genes that are crucial for mitochondrial and autophagy function. For instance, late and early-onset PD associated to mutations in LRRK2 and PRKN genes, responsible for the most frequent dominant and recessive inherited forms of PD, have emerged as promising examples of disease due to their established role in commanding bioenergetic and autophagic balance. Concomitantly, the development of animal and cell models to investigate the etiology of the disease, potential biomarkers and therapeutic approaches are being explored. One of the emerging approaches in this context is the use of patient’s derived cells models, such as skin-derived fibroblasts that preserve the genetic background and some environmental cues of patients. In these PD cell models deficient mitochondrial function and impaired autophagic flux may be determinant in accelerated nigral cell death in terms of limitation of cell energy supply and accumulation of obsolete and/or unfolded proteins or dysfunctional organelles. The reliance of neurons on mitochondrial oxidative metabolism and their post-mitotic nature, may explain their increased vulnerability to undergo degeneration upon mitochondrial challenges or autophagic insults. In this scenario, proper mitochondrial function and turnover through mitophagy, are gaining in strength as protective targets to prevent neurodegeneration, together with the use of patient-derived fibroblasts to further explore these events. These findings point out the presence of molecular damage beyond the central nervous system and proffer patient-derived cell platforms for the study of disease etiopathogenesis and therapeutic approaches focused on modifying the natural history of PD through, among others, the enhancement of mitochondrial function and autophagy.